Energy Balances and Electricity Profiles 2002 - United Nations (United Nations, 2006)
This is the twelfth issue of Energy Balances and Electricity Profiles published by the Statistics Division of the United Nations Secretariat. Like previous issues, this 2002 volume presents energy data for selected countries in a format which shows the overall picture of energy production, conversion and consumption for fuels utilised in the country. Such a publication is useful in assessing and analysing production and consumption patterns in detail on an internationally comparable basis.